Scriptural Truth, Ecclesial Authority and the Challenge of Lay Reception - Wilbert Evensus (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This article examines the pastoral phenomenon among the faithful, who firmly believe in the truth and infallibility of the Scriptures without feeling the need to interpret or explain the texts themselves. Based on limited interviews conducted, this study finds that this phenomenon does not arise from a lack of faith but rather from the Church’s teaching that emphasizes the authority of the Scriptures without allowing space for personal interpretation. The results of these interviews are combined with patristic sources and modern theological discussions to delve deeper into the integration of the truth of the Scriptures into the daily practice of the faithful. A tendency toward clerical interpretation has been found to hinder the sensus fidei, or the communal sense of faith, leading to an exaggerated fear of possibly misinterpreting the Scriptures. Therefore, an inclusive pastoral approach is needed, including through digital and catechetical media, to encourage the faithful to engage with the Scriptures within the bounds of ecclesiastical unity. This aims to ensure that the faith of the faithful is not only a matter of belief but is also practiced with true and comprehensive understanding.